Union and revolution : Scotland and beyond, 1625-1745 - Stewart, Laura A. M.; Nugent, Janay (New history of Scotland, 2020)
A provocative new account of Scotland's history across a century of revolution and political instability Encourages a holistic view of early modern Scotland Relates Scotland's political, socio-economic, and cultural development to the formation of the British imperial state, European and transatlantic migration, and the expansion of global tradePart 1 covers political developments in Scottish history between the accession of King Charles I in 1625 and the destruction of the Jacobite cause in 1745Part 2 takes a thematic approach investigating the social structures, beliefs, customs, and forms of self-representation that shaped how people understood and engaged with politicsUnion, war, conquest, revolution, attempted invasions, and armed rebellions: this was an eventful time even by the standards of Scotland's turbulent history. At the same time, traditional notions of kinship and community came under strain as profound economic changes reshaped social relations and created new opportunities. Laura A. M. Stewart and Janay Nugent explore the creative volatility of the Anglo-Scottish relationship within a European and transatlantic context. Scotland's integration into the burgeoning British imperial state proved easier for some than others; it also drew Scots into the global slave trade. This is a stimulating account of a contentious period, knowledge of which is crucial for an understanding of British history and the politics of today.This edition in the New History of Scotland series radically updates Rosalind Mitchison's Lordship to Patronage (1983), covering Scotland's history, 1625-1745.